2015
DOI: 10.1590/1678-775720140371
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between implant and orthognathic surgery for the rehabilitation of edentulous cleft palate patients: a case report

Abstract: A 43-year-old woman with a unilateral cleft lip and palate, presenting a totally edentulous maxilla and mandible with marked maxillomandibular discrepancy, attended the Prosthodontics section of the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo for treatment. She could not close her mouth and was dissatisfied with her complete dentures. Treatment planning comprised placement of six implants in the maxilla, four in the mandible followed by prostheses installation and orthognathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
5
0
3
Order By: Relevance
“…This surgery for dentofacial deformity correction is performed after the conclusion of facial growth (18) , which justified the sample having mean age of 24 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This surgery for dentofacial deformity correction is performed after the conclusion of facial growth (18) , which justified the sample having mean age of 24 years.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be associated to the fact that changes are perceived by individuals when cleft lip and palate and dentofacial deformities were repaired, leading to positive impact on QoL (18) . In some studies, using the WHOQOL, it was found that, in general, individuals with cleft lip and palate show good QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery objective is to heal maxillomandibular discrepancies once the orthodontic treatment was not enough to correct skeletal disharmony and of the soft tissue (19) . This kind of surgery intervention turns it possible the facial harmony, balanced occlusion and recovery of functional standards (20,21) . The comparison of the obtained results of the pre and post-surgery assessment for the construct validation, showed differences for the following aspects: occlusion, cheeks, tongue, breathing and speech/voice analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Essa sequela impede o crescimento maxilar adequado, resultando em hipoplasia maxilar e deformidade dentofacial do tipo Classe III de Angle (LOPES et al, 2015;LURENTT et al, 2012;YAMAGUCHI, LONIC, LO, 2016;YUN et al, 2015).…”
Section: Introductionunclassified
“…Nesses casos o tratamento ortodôntico isolado não é suficiente para correção do problema e a cirurgia ortognática deve ser associada a fim corrigir discrepâncias maxilomandibulares ao fim do crescimento facial possibilitando uma oclusão estável e o reestabelecimento de padrões funcionais e harmonia facial (FREITAS et al, 2012;LOPES et al, 2015;YUN et al, 2015).…”
Section: Introductionunclassified